2005
DOI: 10.1021/ic048698v
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Transfer Reactivity of Five-Coordinate CH3CoIIIPc

Abstract: CH3CoIIIPc (Pc = dianion of phthalocyanine) has been characterized by equilibrium studies of its trans axial ligation and cyclic voltammetry as a relatively "electron poor" model of methylcobalamin, which in noncoordinating solvents persists as a five-coordinate complex. Axial base (N-donors, PBu3, SCN-, weakly binding O-donors) inhibition of methyl transfer from CH3CoIIIPc shows that the reaction proceeds via the reactive five-coordinate species, even in coordinating solvents. The virtual inactivity of six-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
71
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(81 citation statements)
references
References 75 publications
10
71
0
Order By: Relevance
“…23 If PMF Odemethylation is catalyzed by the Co-corrinoid system, it would be a demethylase with the largest substrate binding site, because it can metabolize 3,5,7,3′,4′-PMF. Because the Co-corrinoid system is inhibited by cyanide and alkyl iodide, 34,35 KCN and alkyl iodide were added to the cell culture metabolizing 5,7-DMF (Figure 8). All three compounds inhibited the demethylation of 5,7-DMF in a concentration-dependent manner, which strongly suggested that the demethylation of PMFs is catalyzed by a Co-corrinoid enzyme.…”
Section: ■ Discussionmentioning
confidence: 99%
“…23 If PMF Odemethylation is catalyzed by the Co-corrinoid system, it would be a demethylase with the largest substrate binding site, because it can metabolize 3,5,7,3′,4′-PMF. Because the Co-corrinoid system is inhibited by cyanide and alkyl iodide, 34,35 KCN and alkyl iodide were added to the cell culture metabolizing 5,7-DMF (Figure 8). All three compounds inhibited the demethylation of 5,7-DMF in a concentration-dependent manner, which strongly suggested that the demethylation of PMFs is catalyzed by a Co-corrinoid enzyme.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In order to understand the enzymatic reaction mechanism, it is essential to consider the effects on the electronic and structural properties of the corrin framework as well as the axial ligand. To evaluate the chemical properties of the corrin framework, two characteristic cobalt corrinoids, di- and tetradehydrocorrin cobalt complexes, have been reported as models of cobalamin . The former cobalt complex is capable of forming a stable Co­(III)–C bond similar to that of methylcobalamin.…”
Section: Introductionmentioning
confidence: 99%
“…The latter cobalt complex (Figure b) provides a stable Co­(I) species, but the subsequent alkylation reaction does not occur in organic solvents . Furthermore, several substituted cobalamins with substitution at the 10-position of the corrinoid and cobalt corrole derivatives have also been synthesized to investigate the framework effect using theoretical and experimental methods. , In addition to the framework effect, various cobalamin derivatives were synthesized to investigate the axial-ligation effect, particularly the relationship between the Co­(III)–C and Co­(III)–N bond lengths. ,, A bulky axial ligand such as DMB is known to cause elongation of the Co­(III)–C bond due to upward folding of the corrin ring. , This axial ligation generally promotes homolytic cleavage of the Co­(III)–C bond as a result of electronic stabilization of the produced Co­(II) species. , In contrast, there are few appropriate cobalamin models which replicate the DMB-off/His-on ligation which occurs in the reaction cycle of methionine synthase, where the methyl group bound to the cobalt atom is transferred to homocysteine via the heterolytic Co­(III)–C bond cleavage. , To evaluate the effect of the histidine ligation, it is of interest to construct a conjugate model between a cobalt complex and a protein matrix. ,, In our previous work, myoglobin reconstituted with tetradehydrocorrin cobalt­(II) complex, rMb­(Co II (TDHC)), was prepared to replicate the cobalamin-binding domain of methionine synthase, because the heme pocket of myoglobin possesses a potent histidine (His93) ligand which coordinates to heme in the native protein. The X-ray crystal structure analysis reveals that the His93 residue coordinates to the Co­(II) corrinoid, and then reduction of the crystals leads to the tetracoordinated Co­(I) corrinoid after deligation of the His93 residue in the heme pocket .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, characteristic imidazolate-like histidine ligation to the cobalamin cofactor is observed in the abovementioned methionine synthase as well as in methylmalonyl-CoA mutase and glutamate mutase [16][17][18][19][20]. Over the past decades, several model systems have been reported using cobalamin and its derivatives as well as cobalt corrinoid complexes [20][21][22][23][24][25][26][27][28]. Previously, our group reported the structure, reactivity and physicochemical properties of myoglobin (Mb) reconstituted with Co(TDHC), (TDHC = 8,12-dicarboxyethyl-1,2,3,7,13,17,18,19-octamethyltetradehydrocorrin), rMb(Co(TDHC)), in efforts to develop a useful proteinbased model of cobalamin-dependent methionine synthase [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%